FERTILITY OF ERODATED SOILS AND YIELD OF GRAIN CROPS - Dadakhonova, Dilshoda (Educational Research in Universal Sciences, 2023)
Erosion control is of great importance for the conditions of irrigated agriculture, especially considering that it is here that irrigation erosion occurs, leading to a sharp drop in soil fertility and crop yields.